Surgery without knife: an ideal treatment for lactational breast abscess - Saharan, Amandeep; Dalal, Satish; Singh, Mahavir; Bhatia, Chisel; Chhabra, Tulit (International Surgery Journal, 2017)
Background: Incidence of breast abscess is 0.4 to 11% of all lactating mothers. Traditionally the treatment of breast abscess has been incision and drainage. Recently aspiration under ultrasound guidance is emerging as another treatment option and rapidly replace incision and drainage Methods: Authors carried out a prospective, randomized study involving 50 lactating women with breast abscess. In group A - 25 patients were managed by ultrasound guided needle aspiration and in group B - 25 patients were managed by incision and drainage. Results: In patients of group A, most breast abscesses resolved with one or two aspirations only, with early healing and lesser number of hospital visits as compared to patients in group B. There was no surgical scar and early resumption of breastfeeding was seen in group A. Conclusions: Ultrasound guided percutaneous aspiration is an effective modality of treatment of lactational breast abscess and it should be the first line of treatment, especially for smaller and unilocular breast abscesses while incision and drainage should be reserved for larger and multilocular abscesses with imminent skin changes.